A low phase noise microwave source for high‐performance CPT Rb atomic clock. Issue 17 (26th May 2021) - Li, Xiaodong; Yun, Peter; Li, Qinglin; Ju, Bowen; Yu, Shaoshao; Hao, Qiang; Du, Runchang; Xu, Feng; Li, Wenbing; Gao, Yuping; Zhang, Shougang
Abstract: Phase noise of the frequency synthesizer is one of the main limitations to the short‐term stability of microwave atomic clocks. Here, a low‐noise, simple‐architecture microwave frequency synthesizer for a coherent population trapping (CPT) clock is demonstrated. The synthesizer is mainly composed of a 100 MHz oven‐controlled crystal oscillator (OCXO), a microwave comb generator, and a direct digital synthesizer (DDS). The absolute phase noises of 3.417 GHz signal are measured to be −55 dBc/Hz, −81 dBc/Hz, −111 dBc/Hz and −134 dBc/Hz, respectively, for 1 Hz, 10 Hz, 100 Hz and 1 kHz offset frequencies, which shows only 1 dB deterioration at the second harmonic of the modulation frequency of the atomic clock. The estimated frequency stability of intermodulation effect is 4.7 × 10 −14 at 1 s averaging time, which is about half order of magnitude lower than that of the state‐of‐the‐art CPT Rb clock. Our work offers an alternative microwave synthesizer for high‐performance CPT Rb atomic clock.